E-readiness measurement tool: Scale development and validation in a Malaysian higher educational context - Goh, Pauline Swee Choo; Blake, Damian (Cogent education, 2021)
Increasing complexity towards harnessing the power of ICT on all levels has created uncertainty about higher educational technological capabilities and adequate strategies to develop e-readiness. In this study, an empirically grounded higher education e-readiness questionnaire in the domain of higher education was developed and validated. Exploratory factor analysis (n = 120) followed by confirmatory factor analysis (n = 336) was done which was presented in two forms; covariance model and the structural model. The covariance model showed that the 5 indicators ("Innovativeness", "Infrastructure", "Collaboration", "Learning flexibility", "Student experience") and assigned 24 items were important e-readiness dimensions from the learners' point of view. The structural models validated the previously extracted factors along with their indicators. As a practical tool, the e-readiness tool could assist institutions towards identifying issues that contribute towards e-readiness thereby formulating strategies accordingly. An example of how it can be used as a practical tool is presented in this paper.